Fear of Crime among College Students: A Test of the Shadow of Sexual Assault Hypothesis - Hilinski, Carly M. (American journal of criminal justice, 2009)
Women’s fear of rape and sexual assault has been both theoretically and empirically linked to their fear of other types of crimes, a phenomenon referred to as the shadow of sexual assault hypothesis in past research. This thesis has been supported across specific populations (i.e., the general population of women in the United States and college women in the United States), but the research examining the shadow of sexual assault hypothesis has suffered from methodological limitations. The current research corrected these limitations and performed a test of the shadow of sexual assault hypothesis among college and university students across temporal situations and victim-offender relationships. The findings indicate that women’s fear of rape and sexual assault does impact their fear of nonsexual crimes across temporal situations and victim-offender relationships.